Kesantunan Berbahasa Tokoh-Tokoh Dalam Novel Merdeka Sejak Hati Karya Ahmad Fuadi Serta Pemanfaatannya Sebagai Bahan Ajar Pembelajaran Bahasa Indonesia Di SMA - Sari, Arum; Muhtarom, Imam; Nuraini, Cut (Peneliti.net, 2024)
This research will analyze the linguistic aspects contained in the novel. The novel used as the target of research is the novel Merdeka Since Hati by Ahmad Fuadi. The objectives in this study are (1) Describe the maxim form of the principle of language politeness according to Leech (2014). (2) Describe the use of the results of the analysis of the form of language politeness principles as teaching materials for Indonesian learning in high school. This type of research uses a qualitative approach with qualitative descriptive methods. The subject of this study is the novel Merdeka Since Hati by Ahmad Fuadi, second printing in August 2019. The results of this study show that the novel Merdeka Since Hati has a form of compliance and a form of violation of the principle of politeness in language. The amount of data obtained in this study was 103 data. In the words of the characters in the novel Merdeka Since Hati by Ahmad Fuadi, compliance with the principle of politeness is more found than violations of the principle of politeness in language. Data on compliance with the principle of language politeness were found as many as 71 data, while data on violations as many as 32 data. The following are presented the conclusions of the research results. The use of research results is used as teaching material in the form of handouts in learning Indonesian High School (SMA), namely in class X negotiation text material of the independent curriculum.